2014
DOI: 10.1039/c4lc00379a
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional parallelization of microfluidic droplet generators for a litre per hour volume production of single emulsions

Abstract: This paper looks at the design, fabrication and characterization of stackable microfluidic emulsion generators, with coefficients of variation as low as ~6% and with production rates as high as ~1 L h(-1). This work reports the highest throughput reported in the literature for a microfluidic device with simultaneous operation of liquid-liquid droplet generators. The device was achieved by stacking several layers of 128 flow-focusing droplet generators, organized in a circular array. These layers are interconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 63 publications
0
109
0
Order By: Relevance
“…When a single type of emulsion is needed, the throughput of the droplet production can be improved without increasing the number of syringes or vials by installing a parallelized droplet producer sharing flow inlets. However, the previously developed microfluidic systems for parallel droplet production [30][31][32]34 allow the use of only a single disperse phase and thus have strong limitations in many applications in which a large number of different contents have to be emulsified in parallel such as in material sciences and biochemistry. A second limitation of these systems is due to the fact that they are based on multiple layer microfabrication techniques requiring a large number of inlets and outlets that are merged through connection to a single channel from a superimposed layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a single type of emulsion is needed, the throughput of the droplet production can be improved without increasing the number of syringes or vials by installing a parallelized droplet producer sharing flow inlets. However, the previously developed microfluidic systems for parallel droplet production [30][31][32]34 allow the use of only a single disperse phase and thus have strong limitations in many applications in which a large number of different contents have to be emulsified in parallel such as in material sciences and biochemistry. A second limitation of these systems is due to the fact that they are based on multiple layer microfabrication techniques requiring a large number of inlets and outlets that are merged through connection to a single channel from a superimposed layer.…”
Section: Resultsmentioning
confidence: 99%
“…31,34 A large number of inlets and outlets can be merged by connecting them with a single channel from a second superimposed layer, usable for the mass-production of emulsions. To date, these approaches have limitations for applications in which the number of samples to be emulsified is large.…”
mentioning
confidence: 99%
“…To reduce the droplet generation time, current work is in progress to incorporate parallel droplet generators, which have been described by multiple groups where up to 512 parallel generators have been reported. 28,[31][32][33][34][35] The use of a single droplet generator here did not change the principle of our method, however. For the serial interrogation of the sample at 10 cfu/ml, we counted a total of 1 ml of drops, which took about 1 h. We have recently shown that it is possible to count drops in massively parallel format at a rate of $0.25 million drops/second.…”
Section: Dynamic Range Of Our Methodsmentioning
confidence: 99%
“…inferior to properties of glass, but still acceptable for many applications (Jeong et al, 2016). The most common thermoplastics used for the fabrication of microfluidic chips are the following materials: polycarbonate (PC) (Ogończyk et al, 2010), polymethylmethacrylate (PMMA) (Conchouso et al, 2014), cyclic-olefin copolymers (COC) (Stachowiak et al, 2007), polystyrene (PS) (Li et al, 2012), polytetrafluoroethylene (PTFE, also known under the brand name Teflon ® ), fluorinated ethylene propylene (FEP) (Horka et al, 2016). Prototyping in thermoplastics is usually done by i) micromilling the channels in the plate and bonding it to another plate (Ogończyk et al, 2010); or by ii) 3D printing the appropriate polymer, e.g.…”
Section: Prototyping Methodsmentioning
confidence: 99%